To eliminate the \( y \) terms when combining the equations, we need to find a common coefficient for \( y \) in both equations.
Given equations:
- \( 5x + 3y = 8.50 \)
- \( 3x + 2y = 5.25 \)
Step 1: Multiply the equations
You mentioned multiplying the first equation by 2:
\[
2(5x + 3y) = 2(8.50) \quad \Rightarrow \quad 10x + 6y = 17.00
\]
Now we need to determine what number to multiply the second equation by to eliminate \( y \). The coefficient of \( y \) in the first equation after multiplication is \( 6 \), so we need to make the coefficient of \( y \) in the second equation equal to \( 6 \) as well.
The second equation has a \( 2y \) term, so we will multiply it by \( 3 \):
\[
3(3x + 2y) = 3(5.25) \quad \Rightarrow \quad 9x + 6y = 15.75
\]
Step 2: Write the modified equations
Now we have two modified equations:
- \( 10x + 6y = 17.00 \)
- \( 9x + 6y = 15.75 \)
Step 3: Subtract the equations
Subtract the second equation from the first to eliminate \( y \):
\[
(10x + 6y) - (9x + 6y) = 17.00 - 15.75
\]
This simplifies to:
\[
10x - 9x + 6y - 6y = 1.25 \quad \Rightarrow \quad x = 1.25
\]
So, the price per pound of apples \( (x) \) is:
\[
\text{Price per pound of apples} = $1.25
\]
Step 4: Substitute to find the price per pound of bananas
Now that we have \( x = 1.25 \), we can substitute this back into one of the original equations to find \( y \). Let's use the second original equation \( 3x + 2y = 5.25 \):
\[
3(1.25) + 2y = 5.25
\]
Calculating \( 3(1.25) \):
\[
3.75 + 2y = 5.25
\]
Subtract \( 3.75 \) from both sides:
\[
2y = 5.25 - 3.75
\]
\[
2y = 1.50
\]
Now divide by 2 to solve for \( y \):
\[
y = \frac{1.50}{2} = 0.75
\]
So, the price per pound of bananas \( (y) \) is:
\[
\text{Price per pound of bananas} = $0.75
\]
Summary
- Price per pound of apples: $1.25
- Price per pound of bananas: $0.75